Effectiveness of Animation Video about Diabetes Mellitus Self-Care Management on The Level of Knowledge among Elderly - Ayu Virda Nita; Mizam Ari Kurniyanti; Ari Dwi Sulaksono (KHD Production, 2024)
Diabetes Mellitus is a common chronic disease among the elderly, and effective self-care management is essential to control this condition. Elderly knowledge about self-care management is important in the care of Diabetes Mellitus. One of the media that can be used to improve knowledge in the elderly is using educational videos. This study aims to evaluate the effectiveness of animated videos about self-care management of diabetes mellitus in improving the knowledge of elderly individuals in RW 01 and RW 02 in Rampal Claket Village, Malang City. The research design used quasi-experimental with pre-test and post-test. The sample in this study was 30 respondents, the sampling technique in this study used purposive sampling technique. The instrument to assess the level of knowledge before and after the animated video intervention using the DMSQ questionnaire. Data analysis used a paired t-test to determine the difference in knowledge scores. The results of this study showed a significant increase in the knowledge of elderly individuals regarding diabetes self-care management after the animated video intervention. The average knowledge score before the intervention was 29.27, which increased to 41.20 after the intervention, an increase of 39.76%. Animated videos have been proven effective in increasing the knowledge of elderly individuals about self-care management of diabetes mellitus with a p-value of 0.000. This study recommends the use of innovative educational media to improve public understanding of chronic disease management.